Reasons for Examine Food Label: A study on Rangpur District - Rahman, Md. Ferdush (Technium Business and Management, 2025)
Food label provide consumers with information which may influence their purchasing decisions. For example, consumers may want to know nutritional properties, what ingredients are in a food product, how to cook it, how it should be stored, use-by date etc . In a rapidly evolving consumer market, where health, safety, quality, economic value, durability etc. are core concerns, food labels are a crucial tool for informed decision-making. This study explores why consumers examine food labels, focusing on five independent variables— economic value perception, health and safety, product identity and traceability, shelf life and durability, quality and assurance, and their impact on label examination and, consequently, purchasing decisions. A conceptual model based on consumer value theory was tested using partial least squares structural equation modeling (PLS-SEM) and survey data collected from 370 consumers in Bangladesh. The results showed that all factors significantly and positively influenced label checking behavior, with product characteristics and quality having the most significant impact. The result also show that health and safety has not significant and positive impact on attitude towards label examination Furthermore, label checking was found to significantly predict purchase decisions, confirming its mediating role between the independent variables and consumer purchase decision. These insights have important implications for policymakers, food manufacturers, and health educators aiming to promote responsible and informed food consumption.